Can speed cameras make streets safer? Quasi-experimental evidence from New York City - Aaron Stagoff-Belfort; Jonathan Ben-Menachem; Brenden Beck (Proceedings of the National Academy of Sciences, 2025)
Each year, approximately 40,000 people die in vehicle collisions in the United States, generating $340 billion in economic costs. To make roads safer without expanding police contact, many cities have turned to automated traffic enforcement, cameras that detect and fine speeding motorists. Does automated enforcement reduce vehicle collisions and injuries? Many previous studies are limited to correlational evidence. By contrast, this study estimates the causal effect of automated enforcement on road safety in a difference-in-differences design. We exploit the staggered rollout of 2,000 speed cameras across New York City between 2014 and 2023, combining data on 700,000 collisions and 200,000 injuries with data on 18 million tickets issued. We find that cameras reduce collisions and injuries by 5 and 2.5% per month on average, respectively. Cumulatively, over the seven months following their introduction, collisions declined by 30% and injuries by 16%.